ANALYSIS OF THE EFFECTS OF FINANCIAL LITERACY AND NUMERACY ON THE FINANCIAL DECISIONS OF MANAGEMENT STUDENTS AT PRIVATE UNIVERSITIES IN JAMBI: DEMOGRAPHIC MODERATION - Setiadi, Henky; Windu, Fitri Novi; Marnas, Marnas (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study analyzed the influence of financial literacy and numeracy on the financial decisions of management students at private universities in Jambi City, examined the moderating role of age, gender, and financial experience, and described students’ levels of financial literacy and numeracy. Using an explanatory quantitative approach, students were selected from five private universities in Jambi City through Disproportionate Stratified Random Sampling, and the data were analyzed using multiple regression and Moderated Regression Analysis with Robust Standard Errors correction. Results show that financial literacy and financial numeracy positively and significantly affect financial decisions, both partially and simultaneously, while age, gender, and financial experience do not moderate either relationship. Students' financial literacy and numeracy levels fall into the moderate to good category. These findings confirm that strengthening financial literacy and numeracy should be a uniform priority in student financial education, regardless of demographic subgroup. Keywords: Financial Literacy; Financial Numeracy; Financial Decision; Demographic Factors; Management Students